1988
DOI: 10.1111/j.1570-7458.1988.tb01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interaction between Cotesia kazak and Hyposoter didymator, exotic parasitoids of Heliothis armigera

Abstract: Competitive interaction between two introduced parasitoids ofHeliothis armigera (Hb.) i.e. the braconid Cotesia kazak Telenga and the ichneumonid Hyposoter didymator (Thunb.) was studied in the laboratory. C. kazak and/-/, didymator individually parasitized about 55~ H. armigera larvae, the combination of the two parasitoids gave more than 7507o parasitism. C. kazak was found to be more effective, when the host was exposed to both parasitoids at the same time, reduced H. didymator population by 69070 to 24 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…Reitz (1996) reported with reference to tachinid parasitoids Eucelatoria bryani Sabrosky and E. rubentis (Coquillett), gregarious tachinid parasitoids of Helicoverpa zea (Boddie), that presence of similarly aged heterospecific competitors often resulted in prolonged developmental time for both competing species. However, Jalali et al (1988) observed no significant differences in the developmental times of C. kazak and H. didymator, larval parasitoids of H. armigera when they were parasitising alone in comparison to that in interaction treatments. In the present study, no significant differences were observed between the treatments where the parasitoids were allowed to parasitise singly and the interaction treatments, with respect to developmental time (from parasitism to cocoon formation) of C. chlorideae (8.4-10 days) (df=12,39; F=1.35; p=0.23) and of E. argenteopilosus (13.3-16.5 days) (df=10,33; F=0.66; p=0.76).…”
Section: Individual Exposure Methodscontrasting
confidence: 64%
See 3 more Smart Citations
“…Reitz (1996) reported with reference to tachinid parasitoids Eucelatoria bryani Sabrosky and E. rubentis (Coquillett), gregarious tachinid parasitoids of Helicoverpa zea (Boddie), that presence of similarly aged heterospecific competitors often resulted in prolonged developmental time for both competing species. However, Jalali et al (1988) observed no significant differences in the developmental times of C. kazak and H. didymator, larval parasitoids of H. armigera when they were parasitising alone in comparison to that in interaction treatments. In the present study, no significant differences were observed between the treatments where the parasitoids were allowed to parasitise singly and the interaction treatments, with respect to developmental time (from parasitism to cocoon formation) of C. chlorideae (8.4-10 days) (df=12,39; F=1.35; p=0.23) and of E. argenteopilosus (13.3-16.5 days) (df=10,33; F=0.66; p=0.76).…”
Section: Individual Exposure Methodscontrasting
confidence: 64%
“…Jalali et al (1988) reported that when larvae of H. armigera were parasitised by the braconid Cotesia kazak (Telenga) and the ichneumonid Hyposoter didymator (Thunberg), C. kazak was more effective and reduced H. didymator population by 69% in 24 h time interval. Godwin and Odell (1984) reported that in the gypsy moth (Lymantria dispar L.) larvae, which were multiparasitised by tachinid parasitoids, Parasetigena silvestris (Robineau-Desvoidy) and Blepharipa pratensis (Meigen), the former suppressed the latter by 65%.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This is mainly attributable to the inability of coexisting parasitoids to distinguish between unparasitized and previously parasitized hosts, which led to direct intrinsic competition (Fisher 1971;Force 1974;Jalali, Singh, Ballal, and Kumar 1988;Strand, Johnson, and Culin 1990). Competition among introduced natural enemies or between introduced and native natural enemies can be of great importance in ecological community dynamics and is particularly important for biological control (Yamamoto, Henderson, Corley, and Iwabuchi 2007).…”
Section: Introductionmentioning
confidence: 99%